2011
DOI: 10.1513/pats.201012-069ms
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Proteomic Strategies toward the Early Detection of Lung Cancer

Abstract: TennesseeSince the advent of the new proteomics era more than a decade ago, large-scale studies of protein profiling have been exploited to identify the distinctive molecular signatures in a wide array of biological systems spanning areas of basic biological research, various disease states, and biomarker discovery directed toward therapeutic applications. Recent advances in protein separation and identification techniques have significantly improved proteomics approaches, leading to enhancement of the depth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…To date the large majority of these biomarkers have been identified as peptides or proteins. Proteomic analytical techniques (Yanagisawa et al 2003, Hassanein et al 2011 have been used in the study of lung cancer, and this has yielded protein biomarkers that have been demonstrated to have high specificity in a study of 54 individuals diagnosed with NSCLC (Zeng et al 2011). Serologic biomarkers of lung cancer have emerged recently: these include carcinoembryonic antigen, the cytokeratin 19 fragment CYFRA21-1, cancer antigen CA-125 (Cedres et al 2011), plasma kallikrein (Chee et al 2008), progastrin-releasing peptide (ProGRP), and neuron-specific enolase (NSE) (Wojcik et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To date the large majority of these biomarkers have been identified as peptides or proteins. Proteomic analytical techniques (Yanagisawa et al 2003, Hassanein et al 2011 have been used in the study of lung cancer, and this has yielded protein biomarkers that have been demonstrated to have high specificity in a study of 54 individuals diagnosed with NSCLC (Zeng et al 2011). Serologic biomarkers of lung cancer have emerged recently: these include carcinoembryonic antigen, the cytokeratin 19 fragment CYFRA21-1, cancer antigen CA-125 (Cedres et al 2011), plasma kallikrein (Chee et al 2008), progastrin-releasing peptide (ProGRP), and neuron-specific enolase (NSE) (Wojcik et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative/quantitative analysis of highquality clinical biospecimen (e.g., tissue and biofluids) of human cancer proteome landscape can potentially reveal protein/peptide biomarkers responsible for this disease by means of their altered levels of expression, PTMs as well as diff erent forms of protein variants. Despite technological advances in proteomics, major hurdles still exist at every step of the bio marker development pipeline [52][53][54][55][56][57][58][59][60][61][62][63].…”
Section: Important and Current Implications Of Phosphoproteomics In Dmentioning
confidence: 99%
“…In addition to understanding roles of metabolites and signaling molecules (Anderson et al, 2016; Sakane et al, 2017), proteome wide identification and quantification of proteins is considered pivotal for elucidating mechanisms underlying biological systems and pathological states (Bantscheff et al, 2012; Hassanein et al, 2011). For this purpose tandem mass spectrometry (MS/MS)-based quantification using isobaric labels such as isobaric tags for relative and absolute quantification (iTRAQ) (Ross et al, 2004) and tandem mass tags (TMT) (Thompson et al, 2003) were introduced (we will refer to these as isobaric tags below).…”
Section: Introductionmentioning
confidence: 99%